2013
DOI: 10.3109/10428194.2013.794267
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Agent Orange exposure on presentation and prognosis of patients with chronic lymphocytic leukemia

Abstract: Exposure to Agent Orange (AO) and the contaminating chemical 2,3,7,8-Tetrachlorodibenzodioxin (TCDD) has been associated with the development of chronic lymphocytic leukemia (CLL). Of the195 veterans diagnosed with CLL from 2001–2010 in a retrospective cohort from the Minneapolis VA, 33 (17%) were exposed to AO. Prognostic factors including Rai stage, lymphocyte doubling time and cytogenetics did not differ between exposed and unexposed patients. Exposed patients were younger at diagnosis (61 vs 72 years, p=0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Although found in young patients, LCL is not rare in 30 to 40-year-old patients [30]. The clinical incidence is not very different from our descriptions above, with less than sick individuals who have suffered from attacks, scarce incidence of hemolytic state and initial infection.…”
Section: Discussioncontrasting
confidence: 53%
“…Although found in young patients, LCL is not rare in 30 to 40-year-old patients [30]. The clinical incidence is not very different from our descriptions above, with less than sick individuals who have suffered from attacks, scarce incidence of hemolytic state and initial infection.…”
Section: Discussioncontrasting
confidence: 53%
“…The US Department of Veterans Affairs has accepted that exposure to Agent Orange is a risk factor for CLL, which has enabled veterans with CLL to claim benefits if they were previously exposed to Agent Orange while in military service 33 . In addition, evidence suggests that exposure to insecticides might be a risk factor for CLL 34 .…”
Section: Epidemiologymentioning
confidence: 99%
“…The median age at CLL diagnosis in our study was 57 years compared to the median age at diagnosis in the US of 72 years . A recent study of 195 adult veterans who were exposed to Agent Orange and developed CLL showed no differences between the exposed and non‐exposed for Rai staging, lymphocyte doubling time, cytogenetic changes or survival . However, the Agent Orange exposed veterans were both significantly younger at time of diagnosis and the latent period was significantly shorter than it was for the non‐exposed veterans.…”
Section: Discussionmentioning
confidence: 97%
“…We were particularly interested in examining the effects of radiation exposures and the age at time of first exposure on the latent period on the basis of two previous reports of apparent alterations in the clinical course of leukemia because of induction by radiation or a chemical . An early report concerning children with acute leukemia from the study of A‐bomb survivors in Hiroshima and Nagasaki indicated that younger age at time of exposure was associated with a shorter latent period prior to the appearance of clinical disease .…”
Section: Discussionmentioning
confidence: 99%